A Bioinspired Synthesis of (±)‐Rubrobramide, (±)‐Flavipucine, and (±)‐Isoflavipucine. (4th July 2016) - Mizutani, Shoma; Komori, Kenta; Taniguchi, Tohru; Monde, Kenji; Kuramochi, Kouji; Tsubaki, Kazunori
Abstract: A biomimetic synthesis of naturally occurring lactams rubrobramide, flavipucine, and isoflavipucine is described. The key step is a regioselective Darzens reaction between isobutyl glyoxal and an α‐bromo‐β‐ketoamide. The construction of the core tricyclic ring system of rubrobramide was achieved by a cascade reaction in a single step from an α, β‐epoxy‐γ‐lactam. Furthermore, the absolute configuration of naturally occurring (+)‐rubrobramide was determined by vibrational circular dichroism. (±)‐Flavipucine and (±)‐isoflavipucine were synthesized from an epoxyimide, which was prepared by reaction of isobutyl glyoxal with a protected α‐bromo‐β‐ketoamide. Deprotection of the epoxyimide and formation of the pyridone ring gave (±)‐flavipucine, which was converted into (±)‐isoflavipucine by thermal isomerization.